In situ based surface-enhanced Raman spectroscopy (SERS) for the fast and reproducible identification of PHB producers in cyanobacterial cultures. Issue 15 (2nd July 2020) - Hermann, Daniel-Ralph; Lilek, David; Daffert, Christina; Fritz, Ines; Weinberger, Simone; Rumpler, Vanessa; Herbinger, Birgit; Prohaska, Katerina
Abstract : Reproducible in situ SERS delivers a significantly reduced analysis time compared to HPLC, allowing timely decisions regarding Synechocystis PHB production. Abstract : The production of polyhydroxybutyrate (PHB) by autotrophic fermentation of cyanobacteria has received increasing interest in the light of carbon emission reducing process strategies. Biotechnological approaches are in development to optimize the yield of PHB, including adapted cultivation media, characterized by a limitation of key nutrients: cyanobacteria accumulate PHB as energy storage molecules under limited growth conditions. Since there is an increasing demand for fast, simple and reliable analytics, we report the establishment of surface enhanced Raman spectroscopy (SERS) as a suitable monitoring tool for up scaled PHB production processes. Both, pure Ag-colloids mixed with bacterial culture, and in situ prepared colloids (Ag- Synechocystis ), generated on the cell surface directly, were successfully applied and evaluated for this purpose. SERS measurements with in situ prepared Ag-colloids improved the reproducibility of Raman signals from 54.8% to 93.9%. The measurement time could be reduced significantly, completing our secondary goal. The quality of classically and in situ prepared Ag-colloids was monitored by zeta potential measurements and scanning electron microscopy (SEM) respectively. For data interpretation and statistical model-building an in house written code in the open source software RStudio was implemented. It was applied for the differentiation of PHB producers at the cellular level, revealing heterogeneities within sample groups regarding the PHB amount accumulated. The results obtained using the statistical model were validated as well and were complementary to the reference HPLC analysis. Therefore, a fast and reliable identification in situ SERS tool for the selection of the most promising cyanobacterial PHB production was established.